The book of Amos and its audiences prophecy, poetry, and rhetoric - Davis, Andrew R. 1978- (Cambridge University Press, 2023)
Many studies of the prophetic books assume that a text's addressee and audience are one and the same. Sometimes this is the case, but some prophetic texts feature multiple addressees who cannot be collapsed into a single setting. In this book Andrew R. Davis examines examples of multiple addressees within the book of Amos and argues that they force us to expand our understanding of prophetic audiences. Drawing insight from studies of poetic address in other disciplines, Davis distinguishes between the addressee within the text and the actual audience outside the text. He combines in-depth poetic analysis with historical inquiry and shows the ways that the prophetic discourse of the book of Amos is triangulated among multiple audiences
Title from publisher's bibliographic system (viewed on 12 Jun 2023)
Keywords: Bible / Amos / Criticism, interpretation, etc